Butenolide Derivatives of Biobased Furans: Sustainable Synthetic Dyes. (15th October 2019) - Saska, Jan; Li, Zheng; Otsuki, Andrew L.; Wei, Jiahui; Fettinger, James C.; Mascal, Mark
Abstract: The dye and pigment manufacturing industry is one of the most polluting in the world. Each year, over one million tons of petrochemical colorants are produced globally, the synthesis of which generates a large amount of waste. Naturally occurring, plant‐based dyes, on the other hand, are resource intensive to produce (land, water, energy), and are generally less effective as colorants. Between these two extremes would be synthetic dyes that are fully sourced from biomass‐derived intermediates. The present work describes the synthesis of such compounds, containing strong chromophores that lead to bright colors in the yellow to red region of the visible spectrum. The study was originally motivated by an early report of an unidentified halomethylfurfural derivative which resulted from hydrolysis in the presence of barium carbonate, now characterized as a butenolide of 5‐(hydroxymethyl)furfural (HMF). The method has been generalized for the synthesis of dyes from other biobased platform molecules, and a mechanism is proposed. Abstract : Synthetische Farbstoffe sind ein weiterer industrieller Rohstoff, der nachhaltig aus Plattformmolekülen hergestellt werden kann, die aus Biomasse gewonnen wurden. Beschrieben wird die Synthese von bio‐basierten Farbstoffen, die starke Chromopore enthalten, die zu leuchtenden Farben im gelben bis roten Spektralbereich führen.